1988
DOI: 10.1177/000348948809700214
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Voices of Patients with Neurologic Disease: Rationale and Preliminary Data

Abstract: This paper presents a rationale for acoustic analysis of voices of neurologically diseased patients, and reports preliminary data from patients with myotonic dystrophy, Huntington's disease, Parkinson's disease, and amyotrophic lateral sclerosis, as well as from individuals at risk for Huntington's disease. Noninvasive acoustic analysis may be of clinical value to the otolaryngologist, neurologist, and speech pathologist for early and differential diagnosis and for documenting disease progression in these vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
15

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 15 publications
5
69
0
15
Order By: Relevance
“…However, this study did not show evidence of changes in the usual frequency range, which is similar to the study of Ramig et al 19 . In the studied periods, it was observed an increase in F0 as Schulz et al 8 that observed an increase in the fundamental frequency in three out of six cases evaluated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, this study did not show evidence of changes in the usual frequency range, which is similar to the study of Ramig et al 19 . In the studied periods, it was observed an increase in F0 as Schulz et al 8 that observed an increase in the fundamental frequency in three out of six cases evaluated.…”
Section: Discussionsupporting
confidence: 91%
“…Frequency perturbation measurements changes are found in PD patients 19 ; NHR also showed increased values. One could suppose that the NHR would be ideal in evaluating changes in the glottal source and less sensitive in analyzing in the dysarthrophonia.…”
Section: Discussionmentioning
confidence: 76%
“…Many pathologies resulted in a decrease fundamental frequency range and could shift fundamental frequency up or down from its baseline value [19][20]. A reduction in habitual loudness has been identified as a salient feature of many speech and voice disorders [21][22].…”
Section: 말소리와 음성과학 제4권 제4호 (2012)mentioning
confidence: 99%
“…17 Acoustic studies further indicate a tendency toward reduced sound pressure level (SPL), reduced voice pitch variability, and phonatory instability, as suggested by increased noise and cycle to cycle variability during phonation. 28,29 Movement velocities and displacements of the velum also tend to be reduced for speech, and acoustic studies suggest increased nasal airflow for speech in as many as 70% of individuals with PD. 22,30 Peak movement velocities and amplitudes of the lips and jaw also tend to be reduced during speech production for persons with PD.…”
Section: Characteristics Of Dysarthria In Parkinson's Diseasementioning
confidence: 99%